Ambiguitas Identitas Visual pada Warisan Budaya Seblak - Aryoseto Satriojati; Iwan Zahar (Syntax Corporation Indonesia, 2024)
Seblak is a traditional Indonesia food that has been widely known, but its visual identity still does not reflect its cultural richness and innovative potential. Using a graphic design approach that involves a qualitative method in the form of a questionnaire for a target audience of more than 30 people, including visual analysis and in-depth interviews with stakeholders, this research aims to redesign a more modern and attractive visual identity using Alina Wheeler's design process. This visual identity focuses on the ambiguous aspect of seblak graphic design which is still said to have no icon or emblem elements that can emit deep cultural values, where these values are able to create relevant and sustainable innovations. The results of the study show that the new visual identity can increase the recognition and attractiveness of seblak restaurants, as well as make a real contribution to social change by strengthening local cultural heritage. Through a strategic design approach, Seblak is expected to reach a wider audience, including the younger generation, and strengthen its position in the global market.